Response of Sorghum (Sorghum bicolor) to applied phosphorous fertilizer in the lowland area of Eastern Amhara - Abushe, Habtemariam Teshome (International Journal on Food, Agriculture and Natural Resources, 2025)
Chemical fertilizers in Ethiopia have made a contribution to crop yield growth to date, although there is potential for further improvement. Phosphorus (P) is an element a primary constituent of plant and animal life. This study was conducted in East Amhara National Regional State of Raya-Kobo and Dawa-Cheffa districts in the 2018 cropping season to verify crop responses to phosphorous fertilizer. The test crop was sorghum (var. Girana one) for both districts. The treatments were: Control, Recommended NP, 50 Kg ha-1NPS, 100 Kg ha-1NPS and 150 kg ha-1 NPS with uniform rate of nitrogen. The design was RCBD and treatments were replicated three times per site. Recommended nitrogen was used uniformly for all treatments. The collected data were subjected to analysis of variance using SAS version 9.0. The Result showed that there was no statistical significance yield difference (p > 0.05) between different rates P fertilizer. Therefore, applying high amount of phosphorous fertilizers for the study districts for the test crops not advisable. But for the maintenance soil phosphorus, 10 Kg ha-1 P is enough.